Job satisfaction and job stress on turnover intention among the academic staffs / Nurazwa Ahmad ... [et al.] - Ahmad, Nurazwa; Patahollah, Noor Nabila; Abu Seman, Noor Aslinda; Kamaruddin, Nor Kamariah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Employee turnover is an upsetting crisis that happens to the organization because it would affect the associated costs and decrease organization performance. There are two types of turnover which are voluntary and involuntary turnovers. Turnover is typically the result of the level of satisfaction and stress experienced by the employees in the workplace. This study is to examine the impact of job satisfaction and job stress on turnover intention amongst academic staff in a public university. This study was performed by employing quantitative research with a total response of 285 academic staffs. SPSS software was used to analyze the data with Pearson correlation and multiple regression analysis to ensure the relationship between and the impact of independent variables on the dependent variable could be determined. The results show a negative relationship of job satisfaction towards turnover intention while job stress shows a weak positive relationship towards turnover intention. Furthermore, it was proven that the R-squared value is 0.084 which clarifies job stress and job satisfaction only represent a small percentage of 8.4% of the turnover intention. Job stress significantly influenced turnover intention at the p < 0.05 whereas job satisfaction significantly influenced turnover intention at p < 0.01. It shows that the academic staff have a low intention to quit their job even if the level of job stress is present. The future study should possibly look into the factors and reasons that influence the academic staffs' decision to stay even though the work they are doing sometimes giving them a hard time.